Indications and results of unicompartmental arthroplasty - Robinson, B; Price, A; Murray, D; McLardy-Smith, P (2003)
There is currently a resurgence of interest in unicompartmental knee replacement (UKR), primarily because of the minimally invasive approach but also because there are now some reports of UKR achieving similar long-term survival rates to total knee replacement (TKR). These improved survival rates are the result of more precise indications, improved implant design, and better surgical techniques. To achieve good 10-year survival with fixed bearing devices, precise indications are necessary; approximately 1 in 10 patients requiring knee replacement are appropriate. The indications are not as narrow when using a mobile bearing device such as the Oxford knee, because of improved wear resistance and instrumentation; approximately one in four patients are appropriate. However, the mobile bearing device is technically more demanding to implant than most fixed bearing devices. There is a vogue to consider UKR to be a preknee replacement. As a result, many new prosthetic designs are being implanted with a minimally invasive approach often with poor instrumentation in a very wide range of patients. It is our belief that those patients who satisfy the accepted indications should be treated with a proven design using sophisticated instrumentation. It remains debatable whether those patients who do not satisfy these indications should have a UKR as a preknee replacement or should have a TKR. © 2003 Lippincott Williams and Wilkins, Inc.